Necessary illusions?: representations of Darfur - Tong, Kathryn Louise (Centre for Film and Media Studies, 2023)
This thesis examined media and NGO representation of the humanitarian crisis in Darfur over an eighteen-month period between January 2004 and June 2005. It concentrated on three key questions. The first question relates to the 'noise' graph of emergencies. What factors - and what actors - were involved in determining the newsworthiness of Darfur? This first key question concerns the graph of media coverage of Darfur, through an escalation phase, an abundant phase, and finally a gradually diminishing phase. Ideally, the diminishing phase of media coverage should correlate with the diminishing stage of the actual emergency. This is rarely the case and so logically other dynamics must exist. The second question examines media representation of the Darfur crisis compared with what was actually occurred. How accurate was the reporting, and what were some of the effects of inaccuracy? The final question is one of perception. To what extent was the crisis in Darfur misperceived; who was primarily responsible for generating that misperception; and was a degree of misperception inevitable? This question encompasses both the representation offered by the international media and that offered by NGO media and public relations departments. The study is framed within the notion of the 'crisis triangle' (UNDP, 1997), which is composed of policymakers, humanitarian actors and the international media. It analyses NGO media functions within the framework of the NGO crisis triangle, composed of internal NGO conflicts between fundraising, advocacy and operational aid. Darfur revealed beyond doubt that the factors involved in determining newsworthiness are complex and, furthermore, not necessarily controlled by any one actor or any one side of the crisis triangle. US political interests significantly contributed to escalating Darfur to the status of 'worst humanitarian crisis in the world', but equally so did the genocide question, and no one actor manipulated the timing of the tenth anniversary of Rwanda to coincide with a campaign of ethnic cleansing taking place in Darfur. One of the most important factors identified was that of simplicity, which explains how media attention was engaged, but not necessarily why. The simplicity also ensured that media and NGO representation of Darfur was unavoidably inaccurate. The media influenced the political will of the international community towards Darfur only indirectly, although it could just as convincingly be argued that the political will of the international community was one of the primary factors influencing the media. There were two identified practical lessons from the examination of the representation of Darfur. The first was that if NGOs were to accept a short-term fall in funding for the longer-term benefit of raising awareness then both a more accurate perception and possibly more sustainable funding could be generated. The second was that if media institutions were to adhere to the Red Cross code of conduct when reporting from disaster situations then a more accurate perception would be generated. This would result in the necessary illusions of disaster reporting not being quite so necessary.